2018
DOI: 10.1186/s12935-018-0689-6
|View full text |Cite
|
Sign up to set email alerts
|

The miR-199a-3p regulates the radioresistance of esophageal cancer cells via targeting the AK4 gene

Abstract: BackgroundMiRNAs was recognized as vital regulators involved in cancer development. Radioresistance remains a major obstacle for effective treatment of cancers. The mechanisms on the miRNA-mediated radioresistance of cancers are still poorly understood. The main subject of this study is to find new miRNA biomarker that regulates the radioresistance of esophageal cancer (EC).MethodsThe cumulative dose of radiation assays were used to screen the EC radioresistant cell lines. Wound-healing and invasion assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…AK4 could modulate anticancer drug sensitivity in lung cancer via the regulation of mitochondrial activity ( 28 ). AK4 could also affect multi-chemoresistance and radioresistance in osteosarcoma and esophageal cancer, and AK4 expression was regulated by miR-199a-3p ( 21 , 29 ). Another study indicated that AK4 also affected the proliferation and invasion of bladder cancer cells in vitro ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AK4 could modulate anticancer drug sensitivity in lung cancer via the regulation of mitochondrial activity ( 28 ). AK4 could also affect multi-chemoresistance and radioresistance in osteosarcoma and esophageal cancer, and AK4 expression was regulated by miR-199a-3p ( 21 , 29 ). Another study indicated that AK4 also affected the proliferation and invasion of bladder cancer cells in vitro ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of AK4 in the progression of multiple types of cancer has been investigated ( 17 21 ). AK4 has been associated with the clinical features of patients with lung cancer and promoted the metastasis of lung cancer by downregulating ATF3 ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐153‐3p enhances the radiosensitivity of human glioma cells by targeting B cell lymphoma‐2 . MiR‐199a‐3p promotes radioresistance in esophageal cancer by targeting adenylate kinase 4 . In addition, miR‐16‐5p enhances the radiosensitivity of prostate cancer cells by modulating the Cyclin D1/E1‐pRb‐E2F1 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…60 Radioresistance in cancer cells causes recurrence of diseases and treatment failure, which is a major clinical obstacle for the treatment by radiotherapy. 61,62 Exosomes modulate the radioresistance of head and neck cancer cells, as indicated by higher overall survival and accelerated DNA repair in cells treated with exosomes isolated from irradiated cells. 63 Exosomes derived from irradiated squamous head and neck carcinoma cells conferred a migratory phenotype to recipient cancer cells.…”
Section: Radiotherapymentioning
confidence: 99%